The influence of Combination Therapy Progressive Muscle Relaxation and Deep breathing Relaxation against Stress Levels of diabetics in Prolanis BPJS The Health Of The City Of Palangka Raya - Barto Mansyah; Ns. Syam’ani (Publisher Cv. Inara, 2021)
Diabetes mellitus is one of the diseases with great impact on health and society, not only for its high prevalence but also for chronic complications and high mortality.. The psychological impact of diabetes began to be felt by the patient since he was diagnosed the doctor. Patients begin to experience psychological disorders such stress on himself related to the care and treatment should be undertaken. Conditions of emotional stress that require proper handling in order not to fall on the more severe conditions. This study aims to identify the influence of combination therapy progressive muscle relaxation and deep breathing relaxation against stress levels of patients with diabetes mellitus in Prolanis BPJS Kesehatan Kota Palangka Raya. The design used in this study using the design of the study : “PRE-TEST-POST-TEST DESIGN WITH CONTROL GROUP”. In this study population was patients with diabetes mellitus in Prolanis BPJS Kesehatan Kota Palangka Raya. The sampling technique in this study using total sampling technique, as many as 48 people. This research is expected to contribute positively to the management of emotional stress in patients with diabetes mellitus.